Penguatan Disain Organisasi dalam Sistem Inovasi Daerah (SIDA) Pasca Covid19 Kabupaten Bandung Barat Propinsi Jawa Barat - Thomas Bustomi (Syntax Idea)
Development of leading sectors through innovation in increasing the competitiveness of leading business sectors. In this study, information was obtained that the West Bandung Regency government had difficulty determining priority leading sectors after the COVID-19 pandemic, where in determining sectoral leading sectors and the need to identify innovation needs in priority leading business sectors. The data collected includes secondary data and primary data through survey interviews and field observations to identify leading sectors through Location Quotient (LQ), Localization Index (LI) and Shiftshare analysis. Based on the analysis, it is obtained that the sectors that have fast growth with high competitiveness are the Education Services sector. Communication, Corporate Service Sector, Health Service Sector and Social Activities and Other Services. In these sectors that have fast growth but need improvement in order to have good competitiveness, it is necessary to have a pattern of relations between various sectors from an innovation system developed through organizational design to map out the process of developing policy relations in and the creation of institutional structures that complement each other in acceleration of West Bandung Regency RPJMD.